Analisis Rasio Likuiditas, Solvabilitas Dan Profitabilitas Sebagai Alat Pengukur Kinerja Keuangan Pada PT. Telkom Indonesia, Tbk Tahun 2017-2021 - Saragih, Rini Maretha; Rokan, Mustafa Kamal; Inayah, Nurul (Universitas Labuhanbatu, 2024)
This study aims to determine how the company's financial performance is assessed through analysis of liquidity ratios, solvency and profitability of the company PT. Telkom Indonesia Tbk in 2017-2021. The research method used is a quantitative descriptive method using measurements of liquidity ratios, solvency and profitability. Based on the research results, the liquidity ratio in 2017-2021 the company's financial performance is said to be not good because the company is unable to cover its short-term liabilities using the company's current assets. Based on the solvency ratio for 2017-2021, the company's financial performance is in good condition, which can be seen from the low percentage of the ratio, which indicates that the company is getting better at paying off its obligations. Based on the profitability ratios for 2017-2021, the company's financial performance is in good condition because the company's ability to generate profits is quite high from sales made by the company.